Physico-chemical characteristics of raw milk from water buffaloes fed moringa (moringa oleifera) leaf meal (MoLM) - Tadeo, Norberto N. Jr.; Vega, Renato SA.; Rayos, Antonio A. (2014)
The study aimed to analyze the nutrient content (protein, lactose, solid-not-fat, and total solid of raw milk from Moringa oleifera leaf meal (MoLM)-fed buffaloes; and compare the effects of MoLM in terms of color, aroma, appearance, flavor and consistency, milk pH, temperature, sweetness, specific gravity, and total titratable acid (lactic acid) of raw milk. A total of eight lactating buffaloes were used as experimental animals for the duration of sixty-three days feeding trial. Treatments include concentrate with 1.25% urea (T1) and concentrate with 30% MoLM (T2). A total of sixty containers of milk samples were used for milk composition analysis and sensory evaluation for the whole sampling period. Collected milk was analyzed by Philippine Carabao Center (PCC) using Milko Scan FT-1 and Fossomatic Minor milk analyzer. Sensory evaluation was performed by PCC using its milk standard. All the data were analyzed using t-test to compare the two treatments.

The results of raw milk analyses from both treatments showed comparative results having a progressive increase in fat, protein, lactose, solid-not-fat, and total solid contents for the initial collection up to the fourth collection of milk. Both treatments had comparable color, aroma, appearance, flavor, and consistency. Slight difference on P value of milk pH, temperature, sweetness, specific gravity, and total titratable acid values were obtained. Statistical analysis showed no significant differences among the treatments observed. Milk produced from MoLM-fed buffaloes is ideal for the production of all dairy products based on the standard set by the PCC. Further, 30% of MoLM can be a good cheap source of protein ingredient for dairy buffaloes.
Keywords: Moringa leaf meal